The Cultural Politics of "Community" and Citizenship in the District Six Museum, Cape Town - Beyers, Christiaan (Anthropologica, 2022)
This paper examines the representation of "community" in the District Six Museum, and its deployment in citizenship struggles in District Six and Cape Town. It discusses the connection between the Museum's participatory project of memorialization, and its positioning in relation to the land restitution and redevelopment process in District Six, as well as in urban reconstruction in Cape Town more broadly.